2004
DOI: 10.1016/j.jphysparis.2005.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Predicting spike times of a detailed conductance-based neuron model driven by stochastic spike arrival

Abstract: Reduced models of neuronal activity such as integrate-and-fire models allow a description of neuronal dynamics in simple, intuitive terms and are easy to simulate numerically. We present a method to fit an integrate-and-fire-type model of neuronal activity, namely a modified version of the spike response model, to a detailed Hodgkin-Huxley-type neuron model driven by stochastic spike arrival. In the Hogkin-Huxley model, spike arrival at the synapse is modeled by a change of synaptic conductance. For such condu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…To account for both types of errors, we defined a stringent coincidence window (δ = 84 µs) and calculated the proportion of coincident spikes in both the recorded and predicted spike trains. We used the gamma factor , a normalized coincidence measure that has been used in a number of studies [30][32]. We optimized the model parameters to maximize on a given recording, and the model performance was then tested on different recordings in the same cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for both types of errors, we defined a stringent coincidence window (δ = 84 µs) and calculated the proportion of coincident spikes in both the recorded and predicted spike trains. We used the gamma factor , a normalized coincidence measure that has been used in a number of studies [30][32]. We optimized the model parameters to maximize on a given recording, and the model performance was then tested on different recordings in the same cell.…”
Section: Resultsmentioning
confidence: 99%
“…This similarity is quantified using the gamma factor () [30], [31], a normalized measure of coincidence between spike trains within a temporal window : is the mean firing rate of the experimental recording, is the number of coincidences between the predicted and recorded spike trains computed within a time window , and denote the number of spikes in the recorded and predicted spike train, respectively. is the expected number of coincidences generated by a Poisson process with rate .…”
Section: Methodsmentioning
confidence: 99%
“…These models have been found to approximate very well the response properties of cortical neurons (Rauch et al, 2003;Giugliano et al, 2004;Jolivet et al, 2006;La Camera et al, 2006) and more biophysically detailed model neurons (FourcaudTrocmé et al, 2003;Jolivet and Gerstner, 2004;Brette and Gerstner, 2005). IF models generally include a fixed absolute refractory period T arp after spike emission.…”
Section: Mpfc Pyramidal Cells Respond As Integrate-and-fire Neuronsmentioning
confidence: 99%
“…Third, cortical neurons in vitro produce responses to white noise currents that share properties of in vivo activity, and Gaussian white noise provides a basic model for the distribution of total current inputs at the soma under conditions of intense synaptic bombardment (Mainen and Sejnowski, 1995;Destexhe et al, 2001;Rauch et al, 2003). Finally, modeling work has shown that, under many circumstances, conductancedriven stimuli produce similar responses to white noise current stimuli: in models that capture key properties of experimentally recorded neurons, the response properties of model neurons driven by conductance stimuli map onto the response properties of equivalent neurons driven by current stimuli (Rauch et al, 2003;Jolivet and Gerstner, 2004;La Camera et al, 2004;Richardson, 2004;Jolivet et al, 2006).…”
Section: Stimulus Designmentioning
confidence: 99%